472P Integration of expression rate and absolute cell counts of PD-1+ stromal tumour-infiltrating lymphocytes: Prognostic significance in esophageal squamous cell carcinoma. (24th November 2019) - Song, Q; Shi, F; Zhou, Q; Chang, H
Abstract: Background: Esophageal squamous cell carcinoma (ESCC) has a poor prognosis in Asian regions and the immunotherapy targeting PD-1 is on the stage of clinical trials. This study aims to investigate the prognostic effect of PD-1 expression in intratumoral and stromal tumor-infiltrating lymphocytes (TILs) on relapse and overall survival of ESCC patients. Methods: A retrospective cohort study was conducted with recruiting 142 ESCC patients who received surgical treatment. Intratumoral and stromal PD-1 expression was tested by immunohistochemistry (IHC). Results: The median follow-up time was 22 months and 21.1% patients were lost of follow-up. Cell counts and expression rate of intratumoral PD1 + TILs did not show any association with disease-free survival (DFS) and overall survival (OS). Expression rate of stromal PD1 + TILs did not have a significant relationship with DFS. The patients with expression rate of stromal PD1 + TILs >20% had the median OS being 19 months and the patients with expression rate ≤20% did not achieved median OS (p = 0.034). The adjusted HR of higher expression rate was 1.49 (95%CI 0.82, 2.60, p = 0.189) for OS. ESCC patients with ≤18 stromal PD1 + TILs/HPF had the median DFS being 10 months however the patients with >18 cells/HPF had the median DFS being 48 months (p = 0.037). The adjusted HR of > 18 stromal PD1 + TILs/HPF on DFS was 0.59 (95%CI 0.35, 1.01, p = 0.055). With reference to the patients of lower expression rate/higher cell counts of stromal PD1 + TILs, patients with lower expression rate/lower cell counts, higher expression rate/higher cell counts, and higher expression rate/lower cell counts, had the adjusted HR for DFS increased to 3.73, 3.36 and 3.99 (p for trend being 0.030) and the adjusted HRs for OS increased to 2.95, 3.64 and 3.82 (p for trend being 0.015), respectively. Conclusions: Integration of expression rate and cell counts of stromal PD1 + TILs had a significant prognostic effect in terms of relapse and overall survival. Further studies are warranted to provide reference for immunotherapy. Legal entity responsible for the study: The authors. Funding: Beijing Hospitals Authority. Disclosure: All authors have declared no conflicts of interest.